Clinical Utility of Elosulfase Alfa in the Treatment of Morquio A Syndrome - Lee CL; Chuang CK; Chiu HC; Tu RY; Lo YT; Chang YH; Lin SP; Lin HY (Dove Medical Press, 2022)
Chung-Lin Lee,1- 5 Chih-Kuang Chuang,6,7 Huei-Ching Chiu,1 Ru-Yi Tu,6 Yun-Ting Lo,5 Ya-Hui Chang,1,5 Shuan-Pei Lin,1,3,5,6,8 Hsiang-Yu Lin1,3- 6,9 1Department of Pediatrics, MacKay Memorial Hospital, Taipei, Taiwan; 2Institute of Clinical Medicine, National Yang-Ming Chiao-Tung University, Taipei, Taiwan; 3Department of Medicine, MacKay Medical College, New Taipei City, Taiwan; 4MacKay Junior College of Medicine, Nursing and Management, Taipei, Taiwan; 5Department of Rare Disease Center, MacKay Memorial Hospital, Taipei, Taiwan; 6Division of Genetics and Metabolism, Department of Medical Research, MacKay Memorial Hospital, Taipei, Taiwan; 7College of Medicine, Fu-Jen Catholic University, Taipei, Taiwan; 8Department of Infant and Child Care, National Taipei University of Nursing and Health Sciences, Taipei, Taiwan; 9Department of Medical Research, China Medical University Hospital, China Medical University, Taichung, TaiwanCorrespondence: Shuan-Pei Lin; Hsiang-Yu LinDepartment of Pediatrics, MacKay Memorial Hospital, No. 92, Sec. 2, Chung-Shan North Road, Taipei, 10449, TaiwanTel +886-2-2543-3535 ext. 3090; +886-2-2543-3535 ext. 3089Fax +886-2-2543-3642Email 4535lin@gmail.com; lxc46199@ms37.hinet.netAbstract: Mucopolysaccharidosis type IVA (MPS IVA or Morquio A) is an autosomal recessive disorder and is one of the lysosomal storage diseases. Patients with MPS IVA have a striking skeletal phenotype but normal intellect. The phenotypic continuum of MPS IVA ranges from severe and rapid progress to mild and slow progress. The diagnosis of MPS IVA is usually suspected based on abnormal bone findings and dysplasia on physical examination and radiographic investigation in the preschool years. In the past, only supportive care was available. Due to the early and severe skeletal abnormalities, the orthopedic specialist was usually the main care provider. However, patients need aggressive monitoring and management of their systemic disease. Therefore, they need an interdisciplinary team for their care, comprising medical geneticists, cardiologists, pulmonary specialists, gastroenterologists, otolaryngologists, audiologists, and ophthalmologists. After the US Food and Drug Administration approved elosulfase alfa in 2014, patients older than 5 years could benefit from this treatment. Clinical trials showed clinically meaningful improvements with once-a-week intravenous dosing (2.0 mg/kg per week), significantly improving the 6min walk test, the 3min stair climb test, and respiratory function when compared with placebo. Elosulfase alfa is well-tolerated, and there is a good response indicated by decreasing urine glycosaminoglycans.Keywords: elosulfasealfa, enzyme replacement therapy, GALNS, lysosomal storage disorder, Morquio A, MPS IVA, mucopolysaccharidosis